A Novel Noninvasive Program for Staging Liver Fibrosis in Untreated Patients With Chronic Hepatitis B. Issue 5 (22nd May 2019) - Chen, Yan; Wang, Yongji; Chen, Yongping; Yu, Zujiang; Chi, Xiaoling; Hu, Ke-Qin; Li, Qin; Tan, Lin; Xiang, Dedong; Shang, Qinghua; Lei, Chunliang; Chen, Liang; et al.
Abstract : OBJECTIVES: Chronic hepatitis B (CHB) can progress into liver fibrosis and cirrhosis with poor outcomes. Early and accurate diagnosis of liver fibrosis/cirrhosis is important to guide the preventive strategy of their related complications. METHODS: A Chinese multicenter cross-sectional study was conducted to develop and validate a novel noninvasive program for staging liver fibrosis in untreated patients with CHB. Liver histology was evaluated independently by 2 pathologists. The alanine aminotransferase ratio, Hepascore, and aspartate aminotransferase to platelet index values were calculated. Liver stiffness measurement (LSM) and diameter of the spleen were measured. Logistic regression with ℓ1 penalty of regression coefficients was used to select the optimal predictors. The diagnostic accuracy for the stage of liver fibrosis was assessed by the area under the receiver operator characteristic curve with 95% confidence interval (CI). RESULTS: A total of 1, 200 patients with CHB were included, of whom 800 and 400 were in training and validation sets, respectively. LSM, platelets, age, hyaluronic acid, and diameter of the spleen were the top 5 predictors associated with any stage of liver fibrosis and integrated into a novel noninvasive program, named as the Chin-CHB score. The area under the receiver operator characteristic curve of the Chin-CHB score was 0.893 (95% CI: 0.77–0.92) for diagnosing significant fibrosis, 0.897 (95% CI: 0.85–0.95) for advanced fibrosis, and 0.909 (95% CI: 0.87–0.95) for cirrhosis. The diagnostic performance of the Chin-CHB score was similar between training and validation sets. The Chin-CHB score had better diagnostic performance than aspartate aminotransferase to platelet index, alanine aminotransferase ratio, LSM alone, and Hepascore for diagnosing any stage of liver fibrosis. CONCLUSIONS: The Chin-CHB score had good diagnostic performance for any stage of liver fibrosis.